2011
DOI: 10.3746/jkfn.2011.40.5.696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Red Ginseng Supplementation on Blood Glucose and Insulin Resistance in Type 2 Diabetic Patients

Abstract: We performed a randomized placebo-controlled trial to determine whether or not fermented red ginseng supplementation modulates blood glucose and insulin resistance in type 2 diabetic patients. A total of 38 patients were randomized to either a fermented red ginseng group or placebo group. The patients in the experimental or placebo group consumed 780 mg of fermented red ginseng or cellulose supplement per day for 12 weeks, respectively. Lifestyle factors and dietary intakes of the patients were not altered dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Ginseng preparations included whole root/rootlets of Korean red, American, or Panax ginseng (4 trials; 25%), and extracts of Korean red, American, or Panax ginseng (10 trials; 62.5%). Two trials (12.5%) did not specify method of preparation [19] , [21] . All the trials used encapsulated powder forms of ginseng as the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginseng preparations included whole root/rootlets of Korean red, American, or Panax ginseng (4 trials; 25%), and extracts of Korean red, American, or Panax ginseng (10 trials; 62.5%). Two trials (12.5%) did not specify method of preparation [19] , [21] . All the trials used encapsulated powder forms of ginseng as the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analyses of systematically removing individual trials showed that removal of five trials individually demonstrating benefits for FBG [7] , [19] , [21] , [22] , [29] led to a loss of significance in the overall effect (MD = −0.16 mmol/L; P = 0.14, MD = −0.27 mmol/L; P = 0.06, MD = −0.28 mmol/L; P = 0.06, MD = −0.28 mmol/L; P = 0.05, MD = −0.23 mmol/L; P = 0.1, respectively). A priori subgroup analyses revealed that the FBG-lowering effects of ginseng were only modified by the diabetes status of the individuals (between-group MD = −0.96 mmol/L [95% CI: −1.44 to −0.47], P = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Despite studies showing no significant improvement in insulin sensitivity and postprandial plasma glucose [35,36], the antidiabetic effect of red ginseng has also been reported via improved glycemic index and insulin sensitivity [37][38][39][40][41]. The effect of reducing HbA1c and insulin resistance and the effect of reducing C-peptide and serum or whole blood glucose were also reported [42,43]. Although the functional role of red ginseng has only been demonstrated on the final phenotype, through this analysis, a list of candidates for experimental investigation for elucidating action mechanisms of red ginseng has been generated.…”
Section: (A)mentioning
confidence: 99%
“…Studies on functional drinks containing red ginseng have been actively investigated. Kim et al (2011a;2011b) presented data on the content and safety of red ginseng beverages. The anti-allergy and anti-inflammatory effects of red ginseng beverages have been reported (Park et al, 2010).…”
Section: Introductionmentioning
confidence: 99%